The impact of power and civic engagement in the decentralized management of natural resources: the case of Turkey - Kadirbeyoglu, Zeynep (2017)
Decentralization is an extensively discussed topic within academic and institutional circles worldwide. While a common argument for decentralization is that it fosters democratic deepening, counterarguments cautiously point to unequal access to resources and distribution of power as factors that inhibit democratization. This study contributes to the literature on the relationship between decentralization and democratization through a comparative study of Water User Associations in two provinces of Turkey and shows in line with the literature that resource and power inequalities hamper the link between decentralization and democratization. However, as this article shows, civic engagement can generate "countervailing power" that can overcome the negative impact of such inequalities
Keywords: Natural resources; Decentralization